A Repercussão do Conceito de Experiência de E. P. Thompson na Historiografia Brasileira: Um Estudo sobre a UNICAMP e Sidney Chalhoub (1980-1998). - Cavalcante, Emanuel Candeia (2013)
This study situated in the research field of History Teaching and Historical Knowledge of the History Post-graduation Course of Universidade Federal da Paraíba, and concentrated in History and Historical Culture has the aim of analyzing the repercussion of the historiography of the English Historian Edward Palmer Thompson in Brazil, specifically, his concept of experience. The period chosen to be analyzed goes from 1980 up to 1998. In order to evaluate how this repercussion movement happened, we dealt with the historiographical production of the Brazilian Historian, Sidney Chalhoub, as well as his contribution as a Professor and the participation of Universidade Estadual de Campinas (Unicamp) as the disseminator and propagator institution of Thompson s historiography in the country. In addition to the history works, we used as resources for this study, the interviews with Chalhoub, the ementas of the programs of the disciplines taught in the History Course of Unicamp in the period of 1980-1998 that were filed in the Secretaria de Graduação da Unicamp. This dissertation has been inspired by the historiographical studies and it is present in the history of historiography.